Primary Intestinal Hodgkins Lymphoma associated with Intussusception and Cholelithiasis - Haque, MM; Siddique, AB; Badruddoza, SM; Manik, MA Hye (TAJ: Journal of Teachers Association, 2009)
Primary intestinal lymphoma is a lymphoproliferative neoplasm of the small intestine. Clinical manifestations are primarily limited to the small intestine. In these cases there is no evidence of lymphoma on chest radiograph, CT scan, peripheral blood or bone marrow puncture. On laparotomy the bowel lesion predominates and few lymph nodes are associated with intestinal lesion. Primary intestinal lymphoma involves the ileum more frequently than jejunum because there is an abundance of lymphoid follicles in the distal small intestine. On the other hand secondary intestinal lymphoma is a manifestation of generalized systemic lymphoid neoplasm. Here we present a very rare case of primary intestinal Hodgkin's lymphoma associated with chronic ileo-caecal intussusceptions and cholelithiasis. doi: 10.3329/taj.v19i2.3156 TAJ 2006; 19(2): 81-83